(untitled) (Biodiversitas Journal of Biological Diversity, 2014)
Rafeie Jahed R, Hosseini SM, Kooch Y. 2014. The effect of natural and planted forest stands on soil fertility in the Hyrcanian region, Iran. Biodiversitas 15: 206-214. In the present work, we studied the effect of natural and planted forest stands on soil fertility in the Hyrcanian region of northern Iran. Natural forest stands (including Acer velutinum Bioss., Zelkova carpinifolia (Pall), Parrotia persica (DC.) C.A.Mey, Quercus castaneifolia C.A. Mey., Carpinus betulus L, Mixed planted stand (including Acer velutinum, Ulmus carpinifolia G. Suckow Quercus castaneifolia C.A. Mey, Carpinus betulus L., Tilia begonifolia Scop. subsp. caucasia (Rupr.) Loria; maple (Acer velutinum Bioss) plantation, pine (Pinus taeda L.) plantation and also clear-cut region (control) were considered in this research. Soil samples were collected at two different depths, i.e., 0-15 and 15-30 cm, and characterized with respect to organic carbon (C), total nitrogen (N), available nutrient elements (P, K, Ca and Mg); pH and soil texture. The results showed that the highest amount of total N was found in mixed plantation. The highest amount of available P was detected in maple plantation and pine plantation had the highest available K and organic C than other treatments. The highest and the lowest available Ca and Mg were found in natural forest and control area, respectively. In addition, it was observed that nutrients accumulate in upper layers of the soil. Hardwood stands have been more successful than the conifers stands, so this should be considered in the sustainable management of forests.